Gender differences and trends in the participation of Malaysian women and men in education - Ahmad, Aminah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This study examined gender differences and trends in the participation of Malaysian women and men in education. Trend data for the period between 1990 and 2007 were calculated and compiled from annual reports of the Ministry of Education, Malaysia. Data on male and female student enrolment in primary, secondary and pre-university and university education, and the distribution of male and female teachers in schools as well as academic staff in teachers' training institutes and polytechnics were presented. The study found that there existed gender differences in the student enrollment in favour of males in vocational and technical schools, as well as in polytechnics. However, in pre-university institutions, teachers training colleges and institutes, and in public universities the proportion of females exceeded the males. Overall the trend in the participation of women in education was very encouraging since the percentages of females in the different levels of education were on the increase while that of males decreased. In terms of specialization, although there were still fewer females in traditionally male-dominated fields such as engineering, architecture, town planning, quantity surveying and vocational skills, the proportions of females in these specializations were on the increase. The females also exceeded the males in the field of science, which encompasses basic science, environmental science, agriculture, home science, food technology, computer science and medicine. The participation of females in the science field steadily increased over the years. There were more females in the arts field which include specializations such as commerce, economics, business, accounting, management, administration, communication, law, social science, humanities and languages, as well as in the field of education, and the proportions in such specializations were on the increase. Implications of the findings on the gender gap in the labour market were discussed.